Development and reproduction of the predator Brontocoris tabidus (Het.: Pentatomidae) fed with Iarvae of the Tenebrio molitor (Col.: Tenebrionidae) - FILHO, PEDRO JUSSELINO; ZANUNCIO, JOSÉ C.; GUEDES, RAÚL N. C.; FRAGOSO, DANIEL B. (Revista Colombiana de Entomología, 2001)
The objectives of this research were to study nymphal development and adult reproduction of Brontocoris tabidus (Signoret) fed with larvae of Tenebrio molitor L. Second instar nymphs of B. tabidus were fed through and also in the adult stage with last instar larvae of T. molitor in the laboratory. During this period reproductive and biological characteristics of B. tabidus were obtained. The duration of the nymphal phase of this predator was 23.7 ± 0.7 days, with the survival of 60.3% ± 4.8% and egg viability of 75.3% ± 1.2%. Results obtained showed satisfactory performance in the development of B. tabidus fed with T. molitor larvae which demonstrated that this predator can be produced in the laboratory when fed with this prey.